Choice and Voice in School Calendar Reform - Shields, Carolyn; Oberg, Steven (Canadian Journal of Education/Revue canadienne de l’éducation, 2000)
Two Ontario elementary schools’ site-based design and implementation of a mod- ified year-round calendar shows the importance of choice and voice in change processes. Interviews and surveys with a superintendent, the two principals, teachers, and parents show how a small structural change may have a large impact on various aspects of school life, including attendance, motivation, and enthusiasm. However, the data demonstrate that there is a point beyond which flexibility and choice may prove inequitable, and in fact may disadvantage some of the people they were intended to serve. La conception sur place et la mise en œuvre d’un calendrier scolaire modifié dans deux écoles primaires ontariennes montrent l’importance du choix et de la par- ticipation dans les processus de changement. Les entrevues et les sondages auprès d’un surintendant, des deux directeurs d’école, des enseignants et des parents indiquent comment un petit changement structurel peut avoir un impact de taille sur les divers aspects de la vie à l’école, notamment sur l’assiduité, la motivation et l’enthousiasme. Les données démontrent toutefois qu’il y a un point au-delà duquel la souplesse et le choix peuvent s’avérer injustifiés et même désavantager certaines des personnes qu’ils devaient accommoder.